Health-promoting ingredients from four selected Azorean macroalgae. (November 2016) - Paiva, Lisete; Lima, Elisabete; Neto, Ana Isabel; Marcone, Massimo; Baptista, José
Abstract: This study presents, for the first time, the nutritional and health promoting aspects of four selected Azorean macroalgae ( Ulva compressa, Ulva rigida, Gelidium microdon and Pterocladiella capillacea ) in terms of total lipids, fatty acids (FA) profile, n6/n3 and hypocholesterolemic (h)/hypercholesterolemic (H) FA ratios, minerals, total essential amino acids (AA), anti-ageing and anti-phenylketonuria AA content, coenzyme Q10, α-tocopherol, total phenolics, antioxidant properties and energy value, on a dry weight basis. The results revealed low lipid content (1.02–4.32%) but significant PUFA content (29.57–69.22% of total FA), suitable FA ratios (0.48–9.49 for n 6/ n 3 and 1.26–4.22 for h/H), balanced macromineral ratios (0.27–1.91 for Na/K and 0.15–1.07 for Ca/Mg), appreciable amount of essential AA (45.27–58.13% of total AA), high amount of anti-ageing AA, low Phe content, coenzyme Q10 (1.25–8.27 μg/g), α-tocopherol (2.61–9.14 mg/100 g), high total phenolic content (27.70–55.07 mg of gallic acid equivalents/g extract), significant free radical scavenging activity (29.32–47.73%) and valuable energy content (6.80–9.80 kJ/g). A regular consumption of these algae either directly or through food supplements may improve human health or may have a protective effect on some diseases and ageing process. They can also be used for producing pharmaceuticals and cosmeceuticals with potential economic value. Graphical abstract: Highlights: Functional ingredients of selected Azorean macroalgae (SAM) are evaluated SAM are rich in MUFA, PUFA, EAA, phenolics, lipophilic antioxidants and energy SAM have healthy ω6/ω3 and h/H FA ratios and suitable Na/K and Ca/Mg ratios SAM have antioxidant properties, high amount of anti-aging AA and low Phe content Intake of SAM allied with pristine seawaters in Azores may improve human health